Introduction to automata theory, language, and computation - Hopcroft, John E. (Pearson/Addison Wesley, 2007)
This classic book on formal languages, automata theory, and computational complexity has been updated to present theoretical concepts in a concise and straightforward manner with the increase of hands-on, practical applications. This new edition comes with Gradiance, an online assessment tool developed for computer science.